Analisis Pengaruh Penggunaan Facebook Terhadap Customer Retention Menggunakan Model Bhatti - Sari, Puspa Tanjung; Riskinanto, Anggar (I-STATEMENT: Information System and Technology Management, 2017)
Social media has become a technology massively used by Internet users. The initial purpose of use that is only for personal needs has evolved toward business. This is especially true of marketing channels in a business. This study aims to know how the use of social media can affect customer retention in social media, especially in Facebook Hydro Coco. It is expected that this study can provide recommendations to social media Facebook Hydro Coco to improve the performance of customer retention relationships. This research uses purposive sampling technique. Data collection was obtained from 184 users of social media users Facebook Fanpage Hydro Coco by providing questionnaires to research subjects focused on adolescents with an age range of 18-24 years. Data analysis technique used in this research is using SEM technique (Structural Equation Modeling) in this case is PLS-SEM. The results of this study showed that there are two factors that affects the social media Hydro Coco Behavioral Intention and Customer Satisfaction. This proves that customers feel satisfaction and have the intention to use the product while using social media Facebook Fanpage Hydro Coco.